Analysis of the variables kinmateic partial distances to run 100, in between and the world record-level Iraqi - Dakhil, Ehab (Journal of Physical Education, 2013)
In the world championships held in Berlin in (2009) for the Athletics the International Federation analyzed the number of the new world race ran 100-meter time of (9.58) achieved by the player Jamaican Usain Bolt, the analysis included all time, partial for every 10 meters and the number of steps performed and the rate of speed, distance increasing speed and maintain the speed and low, and given the importance of the results of this analysis as an analysis of the best and the fastest time achieved in this competition, felt the researcher compared the results of this analysis, the results of analysis of the number of Iraq achieved is to put special points move away figure Iraqi ran 100 meters from the international level. As he was the target of the data collected by the specialist Biomechanics of the International Federation design a mathematical model of the speed and capabilities required for success in the race ran 100 meters, and the other to make way for researchers to others to make comparisons according to these data and compared with levels achieved in their countries, and this point was the importance of this research to identify the fact that differences all global variables and compared the number of the Iraqi National level, in order to determine the physical abilities associated with the emergence of indicators Biomechanics during this race and in accordance with each stage of the technical stages of this race. As is well known that he must be the reaction of hostility is very fast (response and speed of reflectivity) and to be accelerated faster and longer as possible and that up to the highest possible speed (maximum speed) and keep it for as long as possible (maximum bearing speed ) and reduces the loss of speed winning a result of fatigue (less than the maximum bearing speed). And sticking to this basis, the researcher identified the physical abilities in accordance with the indicators Biomechanics obtained from the International Union for the international level and measured by the accounts of the analysis for the local level in order to determine differences between levels and the development of training solutions. The results showed that the local level far from the international level and this requires staff to prepare training programs for the training of physical abilities, according to the results of this search to narrow the gap between international and Iraqi achievements.